2015
DOI: 10.1111/andr.12027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of endogenous metabolites in human sperm cells using proton nuclear magnetic resonance (1H-NMR) spectroscopy and gas chromatography-mass spectrometry (GC-MS)

Abstract: SUMMARYThe objective of this study was to contribute to the first comprehensive metabolomic characterization of the human sperm cell through the application of two untargeted platforms based on proton nuclear magnetic resonance ( 1 H-NMR) spectroscopy and gas chromatography coupled to mass spectrometry (GC-MS). Using these two complementary strategies, we were able to identify a total of 69 metabolites, of which 42 were identified using NMR, 27 using GC-MS and 4 by both techniques. The identity of some of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 46 publications
1
62
0
Order By: Relevance
“…The use of both GC/MS and LC/MS for analysis of AGF allowed the identification of 371 metabolites, some of which have been previously described in sperm and seminal plasma of humans (Paiva et al, 2015; Qiao et al, 2017) and bulls (Velho et al, 2018). GC/MS identified fewer compounds than LC/MS, but this was an expected result because LC analysis does not require the separation of thermally stable and volatile molecules, or large metabolites (Issaq et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The use of both GC/MS and LC/MS for analysis of AGF allowed the identification of 371 metabolites, some of which have been previously described in sperm and seminal plasma of humans (Paiva et al, 2015; Qiao et al, 2017) and bulls (Velho et al, 2018). GC/MS identified fewer compounds than LC/MS, but this was an expected result because LC analysis does not require the separation of thermally stable and volatile molecules, or large metabolites (Issaq et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported in the literature concerning FA profiling in the various settings of sperm characteristics focused on specific compounds, compared limited categories of subjects, included a limited number of samples, and results varied widely (Gulaya et al ., ; Wathes et al ., ; Chavarro et al ., ). With the advancement of technology, it is possible to explore new markers, and new metabolites have been described recently (Paiva et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The association between glycolytic substrates and energy production, which is essential for motility, was determined using metabolomics approach in mouse spermatozoa (Goodson et al, 2012). More recently, using both NMR and gas chromatographymass spectrometry (GC-MS), total of 96 metabolites and more than 10 biological pathways were identified in human sperm (Paiva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%